Benzopyrimido‐pyrrolo‐oxazine‐dione CFTR inhibitor (R)‐BPO‐27 for antisecretory therapy of diarrheas caused by bacterial enterotoxins. Issue 2 (8th November 2016) - Cil, Onur; Phuan, Puay‐Wah; Gillespie, Anne Marie; Lee, Sujin; Tradtrantip, Lukmanee; Yin, Jianyi; Tse, Ming; Zachos, Nicholas C.; Lin, Ruxian; Donowitz, Mark; Verkman, Alan S.
ABSTRACT: Secretory diarrheas caused by bacterial enterotoxins, including cholera and traveler's diarrhea, remain a major global health problem. Inappropriate activation of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel occurs in these diarrheas. We previously reported that the benzopyrimido‐pyrrolooxazinedione (R)‐BPO‐27 inhibits CFTR chloride conductance with low‐nanomolar potency. Here, we demonstrate using experimental mouse models and human enterocyte cultures the potential utility of (R)‐BPO‐27 for treatment of secretory diarrheas caused by cholera and Escherichia coli enterotoxins. (R)‐BPO‐27 fully blocked CFTR chloride conductance in epithelial cell cultures and intestine after cAMP agonists, cholera toxin, or heat‐stable enterotoxin of E. coli (STa toxin), with IC50 down to ~5 nM. (R)‐BPO‐27 prevented cholera toxin and STa toxin‐induced fluid accumulation in small intestinal loops, with IC50 down to 0.1 μg/kg. (R)‐BPO‐27 did not impair intestinal fluid absorption or inhibit other major intestinal transporters. Pharmacokinetics in mice showed >90% oral bioavailability with sustained therapeutic serum levels for >4 h without the significant toxicity seen with 7‐d administration at 5 μg/kg/d. As evidence to support efficacy in human diarrheas, (R)‐BPO‐27 blocked fluid secretion in primary cultures of enteroids from human small intestine and anion current in enteroid monolayers. These studies support the potential utility of (R)‐BPO‐27 for therapy of CFTR‐mediated secretory diarrheas.—Cil, O., Phuan, P.‐W., Gillespie, A.M., Lee, S., Tradtrantip, L., Yin, J., Tse, M., Zachos, N.C., Lin, R., Donowitz, M., Verkman, A.S. Benzopyrimido‐pyrrolo‐oxazine‐dione CFTR inhibitor (R)‐BPO‐27 for antisecretory therapy of diarrheas caused by bacterial enterotoxins. FASEB J. 31, 751–760 (2017). http://www.fasebj.org